Barriers to restoration: Soil acidity and phosphorus limitation constrain recovery of heathland plant communities after sod cutting. Issue 1 (6th January 2020) - Vogels, Joost J.; Weijters, Maaike J.; Bobbink, Roland; Bijlsma, Rienk‐Jan; Lamers, Leon P. M.; Verberk, Wilco C. E. P.; Siepel, Henk
Abstract: Questions: Sod cutting has been used extensively as an effective measure in removing excess N and restoring dwarf shrub dominance in heathlands affected by increased nitrogen deposition. However, recovery of other plant species is often very limited. One barrier is high soil acidity following sod cutting, which results in soil aluminium (Al 3+ ) and ammonium (NH4 + ) reaching toxic concentrations. Sod‐cutting management also removes most of the major nutrients from the system, so intensified nutrient limitation could be an additional barrier to the recovery of species‐rich communities. Soil phosphorus (P) is of special interest as research indicates sod‐cutting management can shift the system to P limitation. Location: Hoge Veluwe National Park, The Netherlands. Methods: We set up a full‐factorial experiment in sod‐cut heathland formerly encroached by Molinia caerulea, adding phosphate (P+) and lime (Ca+) and over the next three growing seasons, we recorded soil chemistry and plant responses. Results: Soil inorganic N, especially soil NH4 +, strongly declined after liming compared to the control situation, confirming that liming alleviates NH4 + toxicity. Addition of P resulted in a similar decline, also suggesting a role for soil phosphate availability in this process. Acid‐sensitive plant species richness increased significantly in both Ca+ and P+ treatment, whereas acid‐insensitive plant species richness only increased significantly as a result of P+ treatment. Mean vegetation relative growth rate increased significantly in both Ca+ and P+ treatments. Conclusions: Excessive P removal due to sod cutting constitutes a second barrier to restoration in addition to soil acidity. We discourage the large‐scale use of sod cutting to reduce soil N availability in heathlands and propose to use interventions that leave the soil nutrient balance intact, such as burning and grazing, mowing or litter removal, in combination with measures that restore the soil buffer capacity. Abstract : Sod cutting is used as measure in heathlands affected by increased nitrogen deposition, but species recovery is often limited. This paper provides experimental evidence for barriers to successful restoration introduced by sod cutting: soil acidity and P limitation. Having important implications for managing ecosystems under high nitrogen load, this advocates a sound N emission reduction instead of N removal policy.